Francis Allison’s success in the district of Magdalena del Mar (2002-2014). An empirical analysis of the incumbency advantage at subnational level - Becerra, María Gracia (2015)
The peruvian political system is characterized by incumbent’s low reelection rates at sub-national level, in that sense, incumbency has been qualified as a disadvantage to politicians in search of reelection. Owing to that, the existence of some cases of mayors that have managed to stay in office for multiple periods of government is surprising; Magdalena del Mar is an exam- ple of it. In this district, Francis Allison has attained reelection in three consecutive elections, obtaining high percentages of vote. For that reason, the present article seeks to explain Allison’s trajectory in the office of district mayor, through political strategies analysis used to manage continuity in office and citizens’ perceptions of themselves. The importance of attributes linked to incumbency are stressed; in that sense, Allison’s success comes from his capacity to satisfy ci- tizens’ needs (using formal and informal governance mechanisms) and from his political ability. To succeeding its aim, the investigation has recourse to data compilation about the municipality; semi-structured interviews to government employees and key actors in civil society; and stratified multistage surveys in the district.